How size, edge shape, functional groups and embeddedness influence the electronic structure and partial optical properties of graphene nanoribbons. Issue 36 (13th September 2021) - Feng, Jin; Mao, Xinlong; Zhu, Hongxia; yang, Zhe; Cui, Mengdi; Ma, Yuchen; Zhang, Dapeng; Bi, Siwei
Abstract : The size, edge shape, functional group and embeddedness affect the properties, including the band structure, excited state energy and electron distribution, of GNRs. Abstract : The armchair and zigzag edge shape makes graphene nanoribbons (GNRs) exhibit interest in different applications. However, the relationship between influencing factors and properties is not clear. Herein, the many-body Green's function theory and the TDDFT method are used to investigate the effect of size, edge shape and functional groups on the electronic and optical properties of GNRs and h-BN-embedded GNRs. We find that ZGNRs have a smaller band gap and absorption edge than AGNRs having the same size and functional groups. The relationship between S1 and T1 is mainly determined by the size and edge shape of GNRs, while the redox ability of water splitting mainly relies on the kind of the functional group. When h-BN is embedded in GNRs, the edge shape of GNRs and the contact part between two substances control the direction of electron transfer in both the ground state and the excited state. These results can provide theoretical support for further improvements and applications of GNRs.